Planning for voice: A skills training manual for women for exercising voice and agency - Kosec, Katrina; Kyle, Jordan; Narayanan, Sudha; Raghunathan, Kalyani (International Food Policy Research Institute, 2023)
The International Food Policy Research Institute (IFPRI), one of the research centers within the global Consultative Group on International Agricultural Research (CGIAR), has a long history of gender research relevant to its mission of reducing poverty and ending hunger and malnutrition. Over the last two decades, gender has been effectively incorporated into all of IFPRI’s strategic research areas and into all phases of research. There is abundant evidence of IFPRI’s role as a leading global think tank on gender issues.